(untitled) (Journal of the College of Education for Women, 2019)
The research risk of flooding on six water basins located in the eastern part of the western plateau, reached total area of the basin (22,998.9 km 2), has reached all the Basin area (basin to time 7056.1 km2 basin by 3585 km 2, Bath Alheiazi 6404 km 2, Abu beasts 544.1 km2 basin Abu Shannan 144.6 km 2, Bath Valley Faraj 5265.1 km 2), where it was specifically spatial degree of this risk by studying some of the hydrological basin transactions directly related to operations spate runoff study area and the occurrence of flood risks on the surface of ponds.